The evolution of the concept of Multifunctional Landscapes: A systematic literature review protocol - Vanegas Cubillos, Martha; Garcia Cornejo, Elena; Moreno Vargas, Diana Cristina; Castro Nunez, Augusto (2024)
This protocol outlines a systematic literature review to explore the evolution and contemporary applications of multifunctional landscapes (MFLs) in rural planning. Initially focused on optimizing agricultural land use, the concept of MFLs has expanded to integrate ecological, social, political, and economic objectives, reflecting a more holistic approach to landscape management. The review aims to trace this evolution and assess how contemporary MFL applications balance economic production, ecological sustainability, and human wellbeing. The methodology follows PRISMA guidelines and includes a systematic search across multiple academic databases to identify relevant studies. Data extraction will focus on key variables such as the definition and conceptualization of MFLs, planning frameworks, challenges and opportunities in balancing diverse objectives, socio-technical innovations, and the spatial and temporal context of the studies. Additionally, the review will analyze trade-offs and synergies between competing goals, methodologies used to assess MFLs, and the role of gender and social equity in MFL outcomes.